Pharmacognosy and the senses in two Amazonian societies - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1999)
Medicinal plant therapy is a total sensory experience among the Matsigenka and the Yora (Yaminahua) of Amazonian Peru. Cues thought to indicate plant efficacy are sensed through multiple modes: taste, odor, irritation, and vision as well as body/mind sensations induced by emetic, psychoactive, and stimulating plants. Though occupying adjacent territories, the Matsigenka and Yora belong to different cultural-linguistic families and did not interact until recently. A comparative study documented criteria used by both groups to evaluate the healing power of plants. Odor is significant in both groups’ cultural constructions of illness and therapy. Both value plants with red juice for blood-related conditions. For the most part, Matsigenka ethnomedicine is allopathic, as medicines act through opposition. Many plants are selected for toxic properties (bitterness, pungency, causticity) that overpower and expel illness. Bitterness is the most frequently encountered medicinal property, and many remedies are administered orally. Yora ethnomedicine is homeopathic in the sense that “like treats like.” Medicinal plants are classified according to visible signatures: spiny plants for sharp pains, pink leaves for pinkeye, plants with watery latex for watery diarrhea, etc.. Medicines are rarely taken internally, but rather applied externally as warm compresses. Bitterness, crucial in Matsigenka models of efficacy, is of little importance in Yora medicine. Different efficacy models appear consistent with different individual and social responses to pain in the two groups. Both groups have suffered severe health consequences and other negative impacts of Western contact in recent decades. Differences in traditional pharmacognosy contribute to different perceptions of Western pharmaceuticals in the two groups. Despite cultural differences, there are major ecological and taxonomic similarities in the two pharmacopoeia. Sixteen botanical families, mostly understory shrubs and herbs, account for more than 65% of all medicines encountered. Regression analysis demonstrates a statistically significant correlation between the two medicinal flora. This study of comparative thnopharmacology reveals neither strict cultural nor environmental determinism in medicinal plant selection, but rather a complex interweaving of cultural and ecological adaptations. Medicines, whether natural or synthetic, indigenous or globally distributed, are at the same time empirically active agents and potent symbols of healing power.
Farmacognosia e os sentidos em duas sociedades amazônicas
Keywords: Antropologia medica; Etnobiologia; Etnobotanica; Amazônia; Etnologia indigena; Antropologia dos sentidos; CNPQ::CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA